Cytopenia and T cell proliferation. - Beverley, P; Linch, D; Callard, R; Worman, C; Cawley, J (1982)
A group of patients with neutropenia or erythroid aplasia associated with T cell proliferation were evaluated to assess the phenotype(s) and functions of T cells observed in these conditions. These patients have near normal numbers of helper/inducer cells but an excess of cells belonging to the suppressor/cytotoxic subset. The characteristic phenotype of these cells is E+, OKT3+, OKT1+1-, OKT8+, Fc gamma R+, and they frequently bear HLA-DR antigen. These cells respond poorly to T cell mitogens and will suppress the response of normal peripheral blood mononuclear cells to mitogens. They fail to suppress PWM-induced immunoglobulin synthesis. Although the natural killer activity in these patients is sometimes low, this subset of T cells possesses cytotoxic capability demonstrable in assays for antibody-dependent cell-mediated cytotoxicity. The evidence for a direct effect of the T cells on BFUE and CFUGM is poor.